Systemic-Communicative Dimensions of Modern Protest (based on German-Language Online Petitions) - L. N. Rebrina (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The results of a study of the characteristics of German-speaking online petitions on the openPetition platform, constituting a spatio-temporal, substantive, collective-personal systemic-communicative dimension of protest; studying the current manifestations of the mediation of politics and Net-thinking as an attribute of modern mediation in the studied communicative practices of protest are presented in the article. The integrative nature of electronic petitions is revealed, which is determined by their multifunctionality, discursive hybridity and stylistic syncretism. The design features in online petitions of a complex addressee (individual addressee and collective co-addressee) and complex addressee (mass and target addressee); relevant communication strategies and tactics of the mass addressee, individual addressee and co-addressees are described. The regularities of the agenda and discursive construction of the problem in online petitions are determined. The methods of forming and maintaining Internet solidarity in the studied protest practice are described. The manifestations of mediation of politics and personality in the analyzed practices are revealed. Attributes and actual reflection in online petitions of a new type of thinking (Net-thinking) as a consequence of the specifics of modern mediation of protest communication are described. The results of the study make a certain contribution to further understanding of the relationship between technological and sociocultural changes.